Risk management of cryptocurrency as a new instrument of savings private individuals’ finance - Protsenko, Vladyslav; Нurzhii Natalia (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. To get the most profit through the use of risk management to predict the state of the cryptocurrency, which will help to better understand the processes that occur with an electronic financial instrument. Design/methodology/approach. The basic principles that have been used in the research are historical, systematic and comparative methods, institutional and structural-functional approaches. Findings. The subject of the article is theoretical, methodological and applies aspects of risk management in cryptocurrency trading in Ukraine. New technologies require careful study. Especially if the technology relates to the sphere of money. As of today, bitcoin serves as an innovative tool for preserving and collecting money for individuals. However, an innovative method of saving and accumulation of money is going to a private face many risks. In order to avoid risks, each person who starts working with cryptocurrency should conduct risk management processes. Only after that, based on the identified risks and methods of their minimization, individuals can store and accumulate their money without unnecessary losses. The term “cryptocurrency” originated in 2009, when Satoshi Nakamoto developed a unique Bitcoin system. It is worth noting that the real name of the person/group of people behind the creation of the project is still unknown. Since then, a large number of citizens of Ukraine and around the world began to track the cryptocurrency rate. Depending on the course, individuals decided what to do with their assets: store, accumulate or sell. Practice has shown that any cryptocurrency is unstable and threatens users with unexpected rises and collapses of the exchange rate. Research limitations/implications. The paper clearly provides direction for application of risk management cryptocurrency in Ukraine to minimize risks. Originality/value. The scientific significance of the work lies in the fact that the study of the application of cryptocurrency risk management takes into account the development of the sphere in Ukraine. Ukraine is one of the leaders in the use of digital currencies in the world. However, in Ukraine, the cryptocurrency is not fixed in the legal field. Citizens suffer from exchange rate jumps of the specified currency, can’t control it and qualitatively analyze prospects of the auction. As a conclusion, it is necessary to intensify the use of risk management in the field of cryptocurrency trading. In practice, this will lead to the fact that it will be possible to minimize the risks of loss of Finance when trading cryptocurrency.